2018
DOI: 10.1159/000492657
|View full text |Cite
|
Sign up to set email alerts
|

SRGN Promotes Colorectal Cancer Metastasis as a Critical Downstream Target of HIF-1α

Abstract: Background/Aims: The chondroitin sulfate proteoglycan serglycin (SRGN), a hematopoietic cell granule proteoglycan, has been implicated in promoting tumor metastasis; however, the underlying mechanisms remain to be elucidated. The present study aimed to investigate the SRGN gene expression and its regulation as downstream signaling of hypoxia-inducible transcription factor 1 alpha (HIF-1α) in colorectal cancer (CRC) cells and tissues. Methods: The expression of SRGN was analyzed in CRC specimens for its correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
(28 reference statements)
1
28
0
Order By: Relevance
“…SRGN encodes the proteoglycan protein, and is mainly expressed in hematopoietic cells. Many studies have confirmed that SRGN promotes tumor invasion and metastasis in colorectal cancer, non-small cell lung cancers, multiple myeloma, nasopharyngeal carcinoma, and breast cancer (Li et al, 2011;Korpetinou et al, 2013;Purushothaman and Toole, 2014;Guo et al, 2017;Xu et al, 2018). SRGN is also involved in inflammatory processes through the regulation of numerous inflammatory mediators such as TNF-α, and activating the NF-κB signaling pathway (Zernichow et al, 2006;Korpetinou et al, 2014;Scuruchi et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…SRGN encodes the proteoglycan protein, and is mainly expressed in hematopoietic cells. Many studies have confirmed that SRGN promotes tumor invasion and metastasis in colorectal cancer, non-small cell lung cancers, multiple myeloma, nasopharyngeal carcinoma, and breast cancer (Li et al, 2011;Korpetinou et al, 2013;Purushothaman and Toole, 2014;Guo et al, 2017;Xu et al, 2018). SRGN is also involved in inflammatory processes through the regulation of numerous inflammatory mediators such as TNF-α, and activating the NF-κB signaling pathway (Zernichow et al, 2006;Korpetinou et al, 2014;Scuruchi et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…NIFK that encodes for a protein that functions in mitosis and progression of cell cycle 26 was found to be upregulated and associated with poor prognosis in lung cancer 49 . SRGN encodes for a proteoglycan in hematopoietic cells 26 and its overexpression is associated with poor prognosis in hepatocellular 50 , colorectal cancer 51 , non-small cell lung cancer 52 , and nasopharyngeal carcinoma 53 . CAMP that is also known as LL37 and CAP18, encodes for cathelicidin antimicrobial peptide 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it has been demonstrated that SRGN can be secreted by various cells including tumor cells [16]. In previous studies, most researches found that high SRGN expression was correlated with low survival rate of most tumors such as breast cancer [33], prostate cancer [34], colorectal cancer [15], nasopharyngeal carcinoma [17], glioma [35], and primary lung adenocarcinomas [36]. However, the role of SRGN in melanoma has not been explored before.…”
Section: Discussionmentioning
confidence: 99%
“…It contains a peptide core of 17.6 kDa which is rich in serine-glycine repeats and has eight glycosaminoglycan (GAG) side chains [11]. A series of evidences have demonstrated that SRGN involves in the progression of tumors including acute myeloid leukemia [12], breast cancer [13,14], colorectal cancer [15], nasopharyngeal carcinoma [16,17], multiple myeloma [18], and etc. [19].…”
Section: Introductionmentioning
confidence: 99%